Sites of tissue binding and uptake in vivo of bacterial lipopolysaccharide-high density lipoprotein complexes: studies in the rat and squirrel monkey. - Munford, R S (1981)
When gram-negative bacterial lipopolysaccharides (LPS) are injected intravenously into the rabbit or rat, they bind to plasma lipoproteins, particularly high density lipoproteins (HDL). The present studies were performed to examine the mechanisms by which LPS-HDL complexes are removed from the circulation and taken up by various tissues. Our approach was to compare the sites of specific tissue binding and uptake of HDL and of LPS-HDL complexes in the rat and squirrel monkey. In the rat, binding of homologous 125I-HDL was demonstrated principally in the adrenal gland, ovary, liver, and spleen. [3H]LPS-HDL complexes (produced in vitro by incubating Salmonella typhimurium [3H]LPS with rat HDL and lipoprotein-free plasma) bound to the same tissues, but with apparently lower affinities. The specificity of binding of both 125I-HDL and [3H]LPS-HDL to these organs was demonstrated in two ways. First, tissue binding of both radiolabeled preparations was swamped out by raising the circulating levels of HDL-cholesterol from 32 to 140 mg/dl. Second, treatment of the animals with dexamethasone abolished specific binding of both HDL preparations to the adrenal gland while administration of adrenocorticotropin increased the specific adrenal binding of the two preparations. The steady-state plasma clearance rate for 125I-HDL equaled 774 +/- 29 microliters/h and was significantly lower (557 +/- 39 microliters/h) for the LPS-HDL complex, a finding that presumably reflected the lesser ability of the various tissues to bind the LPS-HDL complex. Binding studies were also done in the squirrel monkey, an animal that has the same level of circulating HDL cholesterol as the rat, but nearly three times more cholesterol in low density lipoproteins. Specific binding of homologous 125I-HDL and [3H]LPS-HDL was again found principally in the adrenal gland and liver. The results indicate that the sites of tissue uptake of bacterial LPS are strongly influenced by binding of LPS to HDL. In particular, LPS-HDL binding may be an important determinant of the extent to which LPS are taken up by the adrenal gland during bacterial sepsis.